2001
DOI: 10.1128/aac.45.12.3531-3537.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Less Severe Aortic Valve Destruction after Treatment of Experimental Staphylococcal Endocarditis with Vancomycin and Dexamethasone

Abstract: The beneficial effects of therapy combining an antibiotic and dexamethasone have been reported in human studies on meningitis and in experimental studies on septic arthritis, nephritis, and endophthalmitis. Since most patients with staphylococcal endocarditis need a combination of medical and surgical treatment, the purpose of this study was to determine whether the addition of dexamethasone to vancomycin has any beneficial effect regarding the degree of valve tissue damage or the course of experimental aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…In contrast, potential beneficial effects of corticoids on leukocyte recruitment in gram-positive bacterial toxin-induced inflammation have largely been neglected previously. Nonetheless, one study reported that SEA-provoked neutrophil migration is negatively regulated by dexamethasone treatment (9), and more recent data from an experimental study of staphylococcal endocarditis in rabbits demonstrated that there was reduced neutrophil infiltration or aortic valve destruction after combined treatment with vancomycin and dexamethasone (32). However, the anti-inflammatory mechanisms of action of dexamethasone in superantigen-induced inflammation remain elusive.…”
Section: Fig 4 Time-dependent Leukocyte Response To Seb Animals Rementioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, potential beneficial effects of corticoids on leukocyte recruitment in gram-positive bacterial toxin-induced inflammation have largely been neglected previously. Nonetheless, one study reported that SEA-provoked neutrophil migration is negatively regulated by dexamethasone treatment (9), and more recent data from an experimental study of staphylococcal endocarditis in rabbits demonstrated that there was reduced neutrophil infiltration or aortic valve destruction after combined treatment with vancomycin and dexamethasone (32). However, the anti-inflammatory mechanisms of action of dexamethasone in superantigen-induced inflammation remain elusive.…”
Section: Fig 4 Time-dependent Leukocyte Response To Seb Animals Rementioning
confidence: 98%
“…We and other workers have previously demonstrated that treatment with dexamethasone reduces the expression and function of chemokines in response to pro-inflammatory cytokines and thus attenuates leukocyte adhesion and recruitment (16,32,34,42). On the one hand, production of inflammatory mediators and recruitment of leukocytes in response to a gram-negative bacterial toxin, such as lipopolysaccharide, have been extensively studied and, in most reports, have been shown to be sensitive to glucocorticoid treatment (30,40,41).…”
mentioning
confidence: 99%
“…The rabbit model of aortic valve endocarditis was used to evaluate treatment regimens (10,26). The study received a permit from the Veterinary Directorate of the Prefecture of Athens in conformance with Greek legislation in response to EU directive 160/1991.…”
Section: Methodsmentioning
confidence: 99%
“…In one report on experimental MRSA endocarditis, it was found that, immediately after the end of treatment, the severity of valve tissue damage was significantly less in the group receiving dexamethasone (26). However, the possibility that the steroids might delay valve destruction but not prevent it could not be excluded.…”
mentioning
confidence: 99%
“…For those infections within or just below the skin, as well as nonbiofilm septic infections, a robust innate and adaptive inflammatory response seems necessary for clearance. However, in other locations, such as the intramedullary bone infection model in mice (35) and cases of osteomyelitis (29), endocarditis (44), and endophthalmitis (14), a robust response walls the infection off to prevent systemic spread. However, it also forms a nidus of infection that promotes chronic and progressive tissue damage and occasional escape and seeding of other areas.…”
Section: Vol 79 2011 Immune Response To S Aureus Biofilm Infectionmentioning
confidence: 99%